2017
DOI: 10.1017/s1463423617000329
|View full text |Cite
|
Sign up to set email alerts
|

Performance associated effect variations of public reporting in promoting antibiotic prescribing practice: a cluster randomized-controlled trial in primary healthcare settings

Abstract: Public reporting can positively influence antibiotic prescribing patterns of physicians for URTIs in primary care settings, with reduction in antibiotic and combined antibiotic prescriptions. The reduction was mainly attributed to average and high antibiotic prescribers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…Public opinion/expectations and peer comparison appear to influence prescribing behaviours but in contrasting ways depending on the disease, patient cohort and doctor’s ranking. Liu et al [58], Tang et al [59], Tang et al [60], and Yang et al [61] reported effects of public reporting in primary care settings in China. Data on antibiotic prescribing (percentage of prescriptions including antibiotics or injections, and cost) were collected and individual doctors and facilities were compared and rankings were published publicly, e.g., on posters outside facilities.…”
Section: Table A1mentioning
confidence: 99%
See 1 more Smart Citation
“…Public opinion/expectations and peer comparison appear to influence prescribing behaviours but in contrasting ways depending on the disease, patient cohort and doctor’s ranking. Liu et al [58], Tang et al [59], Tang et al [60], and Yang et al [61] reported effects of public reporting in primary care settings in China. Data on antibiotic prescribing (percentage of prescriptions including antibiotics or injections, and cost) were collected and individual doctors and facilities were compared and rankings were published publicly, e.g., on posters outside facilities.…”
Section: Table A1mentioning
confidence: 99%
“…The studies note differences in the effect of public reporting between diseases and age groups according to public perception about appropriateness of prescribing for these categories of illness or people. The intervention also influenced doctors differently according to their ranking, and, in the study by Tang et al [60], doctors categorised as “low prescribers” did not change their habits, even though they could have reduced usage further. These findings indicate that social norms around prescribing are interdependent and must be considered otherwise they can undermine even apparently simple interventions.…”
Section: Table A1mentioning
confidence: 99%
“…Furthermore, as described earlier, public shaming plays a role in efforts to reduce plastic use. This strategy is more difficult to implement in relation to antibiotic use, particularly due to difficulties in identifying levels of 'inappropriate prescribing', although there is some evidence that public reporting of antibiotic prescribing levels can promote reductions in prescribing [74,75]. A closely related, and less ethically problematic, technique is the use of social norm feedback [76,77].…”
Section: Use Social and Reputational Incentives And Sanctionsmentioning
confidence: 99%
“…General practitioners (GPs) were participants of 31 [32, 36, 38, 40, 41, 43, 45, 49, 51, 55, 56, 58, 59, 61-64, 66, 68, 72, 74, 75, 77, 78, 80-82, 85, 90, 92, 96] intervention studies. Participants in the other 38 studies included: (1) Physicians (n=13) [29,33,35,42,48,52,53,69,84,87,88,91,97] , doctors (n=2) [70,83] , clinicians (n=4) [34,39,60,79] , pharmacists (n=4) [44,58,69,76] and staff (n=2) [46,65] of day-care centers; (2) Family physicians (FPs, n=3) [30,37,95] ;…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A total of 22 RCTs were included in the review, including 1 [70] published in Chinese and 21 [29, 30, 33-35, 37, 38, 40, 45, 48-50, 55-58, 61, 66, 78, 92, 96] in English. The studies involved a total of 1,878,693 prescriptions from 14 countries: China [29,48,50,57,70] , Australia [92] , the United States [34] , England [37,38,40] , Canada [33] , Spain [61] , Norway [55] , Germany [45] , Netherlands [30,49,58] , Singapore [78] , Switzerland [35] , Denmark [96] , France [66] and Belgium [56] (951,960 in the intervention group and 926,733 in the control group). Fifteen [29, 30, 33-35, 37, 38, 40, 45, 48-50, 55-57] studies were designed using cluster sampling and 3 [61,92,96] studies did not use random sampling, which was the main reason for the high risk of bias.…”
Section: Intervention Of Apr Studiesmentioning
confidence: 99%